Influence of foot-stretcher height on rowing technique and performance - Buckeridge, E. M.; Weinert-Aplin, R. A.; Bull, A. M. J.; McGregor, A. H. (Sports Biomechanics, 2016)
Strength, technique, and coordination are crucial to rowing performance, but external interventions such as foot-stretcher set-up can fine-tune technique and optimise power output. For the same resultant force, raising the height of foot-stretchers on a rowing ergometer theoretically alters the orientation of the resultant force vector in favour of the horizontal component. This study modified foot-stretcher heights and examined their instantaneous effect on foot forces and rowing technique. Ten male participants rowed at four foot-stretcher heights on an ergometer that measured handle force, stroke length, and vertical and horizontal foot forces. Rowers were instrumented with motion sensors to measure ankle, knee, hip, and lumbar-pelvic kinematics. Key resultant effects of increased foot-stretcher heights included progressive reductions in horizontal foot force, stroke length, and pelvis range of motion. Raising foot-stretcher height did not increase the horizontal component of foot force as previously speculated. The reduced ability to anteriorly rotate the pelvis at the front of the stroke may be a key obstacle in gaining benefits from raised foot-stretcher heights. This study shows that small changes in athlete set-up can influence ergometer rowing technique, and rowers must individually fine-tune their foot-stretcher height to optimise power transfer through the rowing stroke on an ergometer.